Transportation engineering planning and design - Wright, Paul H. (John Wiley & Sons, 1998)
Traveling along the path of the previous editions, "Transportation Engineering Planning and Design," follows the United States transportation system from its development, to its operations and control of the vehicle used to its planning (planning process, data collection, finances, procedures for future developments and evaluation of transportation plans) and on to the design of land, air and water transportation facilities (which includes highways, railways, runways, pipelines, terminals, harbors, ports, lighting for these areas, sizing and more.)